2016
DOI: 10.5812/ijhrba.29149
|View full text |Cite
|
Sign up to set email alerts
|

Dental Health Status of HIV-Positive Patients and Related Variables in Southeast Iran

Abstract: BackgroundDifferent factors can be responsible for the increased prevalence of dental caries and missing teeth in HIV-positive patients.ObjectivesThis study evaluates dental health status and its relationship with social, behavioral, and medical factors in HIV-positive patients under the coverage of Zahedan University of Medical Sciences in Southeast Iran.Patients and MethodsIn a cross-sectional study, the dental health status of 119 HIV-positive patients was assessed in accordance with WHO indices and include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
6
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 35 publications
7
6
3
Order By: Relevance
“…Our data are according to a previous study that reported females have significant lower MCS score, but not PCS [ 31 ]. Our male patients presented significantly lower mean of missing teeth than the females, differing of the results reported by in an Iranian study [ 28 ].…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Our data are according to a previous study that reported females have significant lower MCS score, but not PCS [ 31 ]. Our male patients presented significantly lower mean of missing teeth than the females, differing of the results reported by in an Iranian study [ 28 ].…”
Section: Discussioncontrasting
confidence: 99%
“…In Brazil, DMFT means of 16.9, 17.64 and 18.8 have been reported [ 25 27 ]. These differences in DMFT means can be attributed to hygienic behavioral, access to dental services and socioeconomic status [ 28 , 29 ]. A multivariate linear regression identified age ( P < 0.001) and depression ( P < 0.004) as good and independent predictors of DMFT, even after adjusting for mental health and comorbidities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Though the incidence of HIV-related oral lesions are known to have been reduced from 50% to 10% due to the use of Anti Retroviral Treatment (ART), several studies have shown an increase in the prevalence of dental diseases such as dental caries, periodontitis and tooth wear [6,7]. The Decayed, Missing, Filled Teeth (DMFT) index in PLWHIV ranges from 8.7 to 18.8, depending on the regional, cultural and demographic differences, along with oral health behaviors and preventive practices, nutrition and access to dental services [10].…”
Section: Introductionmentioning
confidence: 99%
“…In a study carried out to investigate the dental status of HIV-positive patients, the overall dental health was poor. Also, a correlation has been found between the age and duration of HIV involvement with the overall dental health status of the participants 10. Barriers that PLWH face in dental settings include complicated administrative work, long waiting times, unwillingness to provide treatment, difficulty to find treating dentists, and having previous psychological problems related to the dental experience 9.…”
mentioning
confidence: 98%